347 SERIAL MONITORING OF LIPID PROFILES IN CHILDREN RECEIVING PRAVASTATIN AFTER RENAL TRANSPLANTATION. (1st January 2005) - Butani, L.
Abstract : Hyperlipidemia is common after renal transplantation (Tx), especially in children, and contributes to the increased cardiovascular morbidity seen in the post-Tx period. Limited data are available on the safety and utility of the 'statins' in improving lipid profiles in children after renal Tx. This 12-month prospective study was undertaken to determine the effect of pravastatin on lipid profiles after renal Tx in children. From 8/01 to 4/04, all 17 newly transplanted pediatric renal Tx recipients at our center were pre-emptively treated with pravastatin from the immediate post-Tx period. Fasting lipid profiles were obtained at 1, 3, 6 and 12 months after Tx. Trends in the lipid profile with time were analyzed using the Repeated Measures General Linear Model (GLM). A matched historical cohort of Tx recipients not treated with pravastatin was used as a control population for comparison. The mean/standard deviation (SD) age of the children at Tx was 8.7 (6.7) years. There were 8 (47%) males; 11 (65%) were Latino, while the remaining were Caucasian. Most patients were receiving tacrolimus and mycophenolate mofetil and all but 2 were also on steroids. Table shows the data on the serial lipid profiles in these children. The GLM analysis showed that with time, there was a statistically significant decline in the total cholesterol, serum triglyceride, LDL and also HDL cholesterol (p value ≤0.005 for each). Compared to the controls, the mean serum cholesterol was lower at all time points post-Tx in the treated patients. However, in spite of treatment, the prevalence of hypercholesterolemia increased from 31% pre-Tx to 53% at 1-month, but declined thereafter to 6% (3 and 6 months) and to 0% at 1year. No child developed any complications related to therapy and none needed drug discontinuation. In summary, pravastatin is safe in the post-Tx period in children and reduces serum cholesterol and LDL cholesterol. A novel observation in our study was the decline in HDL cholesterol with pravastatin. Whether the pre-emptive use of the statins will result in lower cardiovascular morbidity, especially considering the concomitant reduction in HDL cholesterol seen in our study remains to be determined.